Dinamika Ukuran Dewan Direksi, Ukuran Dewan Komisaris, dan Ukuran Komite Audit terhadap Nilai Perusahaan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study analyzes the effect of board of directors size, board of commissioners size, and audit committee size on firm value in the consumer non-cyclical sector listed on the Indonesia Stock Exchange during 2020–2023. The research highlights the importance of corporate governance in enhancing company performance and competitiveness, especially in sectors facing sustainability challenges and strict oversight. A quantitative method was employed using multiple linear regression with a purposive sample of 77 companies. The results show that the size of the board of directors and board of commissioners has a positive and significant effect on firm value, while audit committee size has no significant effect. These findings suggest that the decision-making capacity of directors and supervisory role of commissioners are key to increasing firm value. Conversely, the audit committee’s existence may not contribute meaningfully if it only meets minimum requirements without functional effectiveness. This study implies the need to strengthen governance structures, particularly by enhancing the capacity of boards, to improve firm value and competitiveness.